2006
DOI: 10.1111/j.1399-3046.2006.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience with the use of piperacillin–tazobactam in pediatric non‐renal solid organ transplantation

Abstract: Bacterial infection remains a major problem after solid organ transplantation (SOT), especially in children. Piperacillin-tazobactam (Pip-Tazo) is a beta-lactam-antibiotic combination with a broad spectrum of activity including gram-positive cocci as well as gram-negative rods, non-fermentative and anaerobic bacteria. The aim of this retrospective study was to critically review our experience with Pip-Tazo as perioperative prophylactic agent in pediatric non-renal SOT. Between 1993 and 2003 Pip-Tazo was used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…946 A small, retrospective, single-center cohort study reported outcomes of children undergoing liver, heart, small bowel, or lung transplantation receiving piperacillin-tazobactam 120-150 mg/kg/day beginning before surgical incision and continuing for 48 hours postoperatively and found favorable results, with a superficial SSI rate of 8% and no deep SSIs. 992 Recommendations. The recommended agents for patients undergoing liver transplantation are (1) piperacillin-tazobactam and (2) cefotaxime plus ampicillin ( Table 2).…”
Section: Liver Transplantationmentioning
confidence: 99%
“…946 A small, retrospective, single-center cohort study reported outcomes of children undergoing liver, heart, small bowel, or lung transplantation receiving piperacillin-tazobactam 120-150 mg/kg/day beginning before surgical incision and continuing for 48 hours postoperatively and found favorable results, with a superficial SSI rate of 8% and no deep SSIs. 992 Recommendations. The recommended agents for patients undergoing liver transplantation are (1) piperacillin-tazobactam and (2) cefotaxime plus ampicillin ( Table 2).…”
Section: Liver Transplantationmentioning
confidence: 99%
“…The combination of cefotaxime plus ampicillin has been reportedly used in children undergoing living-related donor liver transplantation; the efficacy of this regimen appeared to be favorable [946]. A small, retrospective, single-center cohort study reported outcomes of children undergoing liver, heart, small bowel, or lung transplantation receiving piperacillin-tazobactam 120-150 mg/kg/day beginning before surgical incision and continuing for 48 h postoperatively and found favorable results, with a superficial SSI rate of 8% and no deep SSIs [992].…”
Section: Pediatric Efficacymentioning
confidence: 99%
“…Wiesmayr et al [15] performed a retrospective study to critically review their experience with piperacillin-tazobactam as well as perioperative prophylactic agent in paediatric non-renal solid organ transplantation. Between 1993 and 2003 piperacillin-tazobactam was used as initial perioperative prophylaxis in 45 paediatric patients who underwent a total of 49 transplants (36 liver, 7 cardiac, 2 lung, and 4 small bowel).…”
Section: Effects Of Piperacillin-tazobactam In Infants and Childrenmentioning
confidence: 99%